Penerapan Metode Iqro Dalam Pembelajaran Al-Quran Di TPQ An-Nur Di Desa Tresnorejo Kecamatan Petanahan - Ana, Nova Ari; Maryanto, Maryanto; Kurniawan, Benny (Tarbi: Jurnal Ilmiah Mahasiswa, 2022)
The research objectives are: (1) to determine the application of the Iqra method in learning the Qur'an at the An-Nur TPA in Tresnorejo Village, Petanahan District; (2) to find out the obstacles faced in the application of the Iqra method in learning the Qur'an at the An-Nur TPA in Tresnorejo Village, Petanahan District. This study used qualitative research methods. This research was conducted within three months. The research subjects were students, and Ustadz/Ustadzah at the Al-Qur'an An-Nur Education Park. Data collection techniques using observation, interviews, documentation, and questionnaires. The data analysis techniques used are data reduction, data presentation and then verification. Based on the results of the study, it can be concluded that: 1) The application of the Iqro method in Al-Qur'an Learning has been going well. The steps for the Iqra method include: opening activities with kiyaman, handshakes, kungudan, khusyuan, and prayer. The main activity of the ustadz is reading readings from the volume book and the students are imitating, the students are listening to the reading of the ustadz. While the closing activity is with prayers and greetings. The core activity contains: the learning process has also been good. Evaluation is carried out every two months and at the end of the year. His trademark beats and tutor teachers. 2) Obstacles in implementation include lack of human resources and youth's interest in teaching. The solution is to find PAI teachers around the neighborhood to teach